Cool Urbanism: The Radiant Exitance City. (3rd January 2023) - White, Marcus; Yang, Tianyi
Abstract: Urban densification is affecting our quality of life – from vitamin D defi ciency due to not enough sunlight reaching us in the tall urban canyons that are created by high buildings, to urban heat islands disrupting our sleep, and many other causes of human irritation. Exploring the Radiant City famously proposed by Le Corbusier in 1930, Guest‐Editor Marcus White, together with Australian architect Tianyi Yang, a researcher and lecturer from Swinburne University of Technology and the University of Melbourne, investigate ways to make the model more workable with pencil‐thin towers.